Treatment of rheumatoid arthritis with chimeric monoclonal antibodies to tumor necrosis factor alpha. - Elliott, M; Maini, R; Feldmann, M; Long-Fox, A; Charles, P; Katsikis, P; Brennan, F; Walker, J; Bijl, H; Ghrayeb, J (1993)
OBJECTIVE: To evaluate the safety and efficacy of a chimeric monoclonal antibody to tumor necrosis factor alpha (TNF alpha) in the treatment of patients with rheumatoid arthritis (RA). METHODS: Twenty patients with active RA were treated with 20 mg/kg of anti-TNF alpha in an open phase I/II trial lasting 8 weeks. RESULTS: The treatment was well tolerated, with no serious adverse events. Significant improvements were seen in the Ritchie Articular Index, which fell from a median of 28 at study entry to a median of 6 by week 6 (P < 0.001), the swollen joint count, which fell from 18 to 5 (P < 0.001) over the same period, and in the other major clinical assessments. Serum C-reactive protein levels fell from a median of 39.5 mg/liter at study entry to 8 mg/liter at week 6 (P < 0.001), and significant decreases were also seen in serum amyloid A and interleukin-6 levels. CONCLUSION: Treatment with anti-TNF alpha was safe and well tolerated and resulted in significant clinical and laboratory improvements. These preliminary results support the hypothesis that TNF alpha is an important regulator in RA, and suggest that it may be a useful new therapeutic target in this disease.